(untitled) (Altre Modernità, 2017)
Great Expectations is probably the most adapted and rewritten work of the Dickensian literary production. Since the author’s adaptation for his public readings, it was clear that the narration was not focused on the love story between Pip and Estella, but on the relationship between the orphan and the convict, his second father. In the last decades numerous transpositions have confirmed that Magwitch, despite his diegetic marginality, is the classic’s most magnetic character: The Boy and the Convict by Aylott (1909), Great Expectations: The Untold Story by Burstall (1987), Magwitch by Noonan (1982), Jack Maggs by Carey (1997), the recent spin-off by Supple, Magwitch (2012), and a self-published trilogy by Lester (2010-2011) feature Magwitch as a main character, to redeem him and to give him a better destiny than Dickens did. After an overview of the reasons for his reception, and a section on the transposing strategies used by rewritings and adaptations, this paper aims at showing the new attention to the theme of fatherhood or parenthood to which this character is strictly related. In particular, keeping in mind Sadrin’s analysis of Great Expectations in terms of the “family romance”, these works shed light on the metaphorical and metonymical meaning of Magwitch’s relationship with Britain and Australia.